Analisis Perlindungan Hukum Pada Wartawan Berdasarkan Undang-Undang Nomor 40 Tahun 1999 tentang Pers - Ragil Hadiwibowo (Indragiri Law Review, 2025)
Press freedom as regulated in the Press Law is a manifestation of popular sovereignty which is based on the principles of democracy, justice and the supremacy of law. In relation to press journalistic activities, in practice there is a journalist profession under the auspices of the press which plays an important role in the input and output of a journalistic work. Neither the press nor journalists in carrying out their duties must face obstacles or restraint from any party, including the government or law enforcement officials. Therefore, journalists in carrying out their profession, whether in the form of searching, obtaining, processing, storing or conveying information in oral, written, data, images and other forms with all types of existing media, such as print media or electronic media, must always receive protection. Legally